2014
DOI: 10.1016/j.dnarep.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and genetic inactivation of tyrosyl-DNA-phosphodiesterase 1 (TDP1) in human lung cancer cells from the NCI-60 panel

Abstract: Tyrosyl-DNA-phosphodiesterase 1 (TDP1) repairs 3’-blocking DNA lesions by catalytically hydrolyzing the tyrosyl-DNA-phosphodiester bond of trapped topoisomerase I (Top1) cleavage complexes (Top1cc). It also removes 3’-blocking residues derived from oxidative damage or incorporation of chain terminating anticancer and antiviral nucleosides. Thus, TDP1 is regarded as a determinant of resistance to Top1 inhibitors and chain terminating nucleosides, and possibly of genomic stability. In the 60 cell lines of the NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…In this study, we extend our initial finding that TDP1 was found inactivated in two of the lung cancer cell lines of the NCI-60 (36) by showing lowest TDP1 expression in NSCLC cancer cell lines and tumor samples, and establishing that both gene copy number defects and promoter hypermethylation cause such defective expression. We also found a broad range of expression of TDP1 across cancer cells (Figure 6 and Supplemental Figure 2).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this study, we extend our initial finding that TDP1 was found inactivated in two of the lung cancer cell lines of the NCI-60 (36) by showing lowest TDP1 expression in NSCLC cancer cell lines and tumor samples, and establishing that both gene copy number defects and promoter hypermethylation cause such defective expression. We also found a broad range of expression of TDP1 across cancer cells (Figure 6 and Supplemental Figure 2).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, leukemia and blood cancers tend to have high TDP1 expression (Figure 6B) while non-small cell lung cancers (NSCLC) have the broadest TDP1 expression range with some cells having background (no significant) TDP1 expression (Figure 6C and Supplementary Figure 2A). In the NSCLC cell lines, we found that lack of TDP1 expression is also driven by promoter hypermethylation (Figure 6D) (36). …”
Section: Resultsmentioning
confidence: 99%
“…TDP1 orthologs exist in all organisms and act both in the nucleus and vertebrate mitochondria (where Top1mt is present [42]) [4346]. Genetic inactivation of TDP1 confers hypersensitivity to camptothecins in human [4750], murine [51,52], and chicken cells [27,45,53], as well as in Leishmania donovani (trypanosome) [46], and in yeast Saccharomyces pombe [54], and S. cerevisiae [41,55]. …”
Section: Tyrosyl-dna Phosphodiesterase 1 (Tdp1)mentioning
confidence: 99%
“…Because TDP1 or TDP2 knockout vertebrate cells show normal cell growth and knockout mice are viable without obvious phenotype [5052,132], it is expected that TDP1 or TDP2 inhibitors will be well tolerated.…”
Section: Tdp Inhibitorsmentioning
confidence: 99%
“…This finding was surprising because TDP1 is not essential for viability in other eukaryotes, including yeast (10,11), chicken and human cells (4,24), and mice (16,25). Here we use an insertional mutant (Exelixis line c03958) to elucidate the role of TDP1 in flies and its critical activity for the repair of 3′-blocked DNA termini and neuroprotection.…”
mentioning
confidence: 99%